2016
DOI: 10.4028/www.scientific.net/amm.847.60
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Glass and Carbon FRCM Composite Materials Applied onto Concrete Supports

Abstract: In recent decades the growing need for strengthening and retrofitting existing structures has led to the development of innovative strengthening materials. Fibre reinforced composites have been shown to be an effective strengthening solution for flexural and shear strengthening and for confinement of axially/eccentrically loaded elements. Fibre Reinforced Cementitious Matrix (FRCM) composites, comprised of high-strength fibres and an inorganic matrix, are a newly-developed type of composite that has better res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…4(b)] shear tests. In single-lap shear tests, a TRM strip is externally bonded to one side of a concrete block, and then a tensile load pulls out the TRM strip while the concrete block is fixed (Sneed et al 2014;Carloni et al 2015;D'Antino et al 2015;Sneed et al 2015;D'Antino et al 2016a, c;Carloni et al 2017;Sabau et al 2017). In double-lap shear tests, TRM strips are bonded to both sides of two concrete blocks that are only connected with TRM strips, and the concrete blocks are subjected to tensile loading up to the failure of the TRM (Ortlepp et al 2006;D'Ambrisi et al 2012;Awani et al 2015;Raoof et al 2016;Raoof and Bournas 2017c).…”
Section: Bond Aspects Of Trmmentioning
confidence: 99%
See 1 more Smart Citation
“…4(b)] shear tests. In single-lap shear tests, a TRM strip is externally bonded to one side of a concrete block, and then a tensile load pulls out the TRM strip while the concrete block is fixed (Sneed et al 2014;Carloni et al 2015;D'Antino et al 2015;Sneed et al 2015;D'Antino et al 2016a, c;Carloni et al 2017;Sabau et al 2017). In double-lap shear tests, TRM strips are bonded to both sides of two concrete blocks that are only connected with TRM strips, and the concrete blocks are subjected to tensile loading up to the failure of the TRM (Ortlepp et al 2006;D'Ambrisi et al 2012;Awani et al 2015;Raoof et al 2016;Raoof and Bournas 2017c).…”
Section: Bond Aspects Of Trmmentioning
confidence: 99%
“…The bonded length was a parameter investigated in most studies (D'Ambrisi et al 2012;D'Antino et al 2013D'Antino et al , 2014Sneed et al 2014;Tran et al 2014;Awani et al 2015;D'Antino et al 2015;Ombres 2015a;Sneed et al 2015;D'Antino et al 2016a;Raoof et al 2016;Sabau et al 2017). It was concluded that ultimate load and bond capacity increase nonlinearly with the bonded length.…”
Section: Bond Aspects Of Trmmentioning
confidence: 99%
“…The test results showed a 30% higher bond capacity in the former, owing to penetration of the mortar through the fabric grid and improved mechanical interlock. In other work, the bond behavior of FRCM composites comprising glass and carbon fabrics was studied using single-lap direct-shear tests [10]. Specimens with a glass fabric exhibited higher peak loads than those of their counterparts with carbon fabric, indicating a better bond for the glass FRCM composites.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of published works reported that the bond capacity increased with the bonded length up to an effective length, after which the bond strength remained constant. In fact, effective bond lengths in the range of 150-300 mm were reported [10,[13][14][15][16][17][18]. Conversely, the bonded width had little or no effect on the bond strength [15,16,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The latter is considered as the most suitable test to characterize the TRM-to-substrate bond behavior due to it easy reproducibility. Depending on the materials' properties, such as nature of the substrate, matrix strength, textile stiffness, the failure mode may interest the substrate-matrix interface, textile-matrix interface, or fiber failure [22][23][24][25]. Moreover, investigations were carried out by adopting plant fibers, such as hemp, flax, sisal, and coir, as reinforcement of TRM systems, showing the latter as a potential solution to increase the sustainability of the systems but still characterized by mechanical issues mainly related to the low stiffness of the textile, adherence properties, and durability aspects [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%